Privacy and Modification of Terrace Housing among Malay Occupants in Klang Valley, Malaysia - Abdul Rahim, Zaiton (2007)
Privacy at home is important for normal functioning of daily activity. However, in the context of housing in Malaysia, there are many opinions which suggest that existing terrace housing is incongruent with the privacy needs of its inhabitants. Inconsistency between the house as a site for privacy, and the occupants results in behavioural adaptation and redefining of privacy needs, which over time, changed the concept of privacy. Due to its importance, privacy is expected to be one of the main reasons for housing modification which has become a Malaysian culture. This research is focused on examining the concept of privacy in the context of housing among Malay families living in terrace housing, and the relationship between privacy and terrace housing design and modification. The research employed a combination of survey interview and case study which uses in-depth interview, analytical review of housing layout drawings and site observation. The research involved 374 respondents for the survey interview and 11 respondents for the case study from three housing schemes in Gombak and Kajang. SPSS (Statistical Package for Social Science Software) was used to analyse data from survey interview. Data from case study were interpreted and transcribed to provide consistent results which complement each of the analyses. The research found that the concept of privacy in the context of terrace housing among Malay families has changed. Privacy of the family is given importance as compared to community ties and individual privacy. The changes are partly attributed to terrace house and housing environment which do not support the privacy needs of Malay family. It was found that at the private level, privacy is most affected by some aspects of terrace housing design particularly the lack of a clear division between the public and private spaces. At the public level, privacy is affected by the overall arrangement of housing units and the external factors of housing environment. Privacy is found to influence housing modification base on the specifics of design attributes modified. However, financial resources of the family, availability of space, individual family’s privacy perceptions and expectations and housing environment influenced the level of privacy achieved after housing modification.